PENGARUH SANKSI PERPAJAKAN, PELAYANAN FISKUS DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI (Studi Empiris Pada Wajib Pajak Orang Pribadi yang Terdaftar di KPP Pratama Jayapura) - Bilha M. F. Mandowally; Theo Allolayuk; Cornelia D. Matani (Fakultas Ekonomi dan Bisnis, Universitas Cenderawasih, 2020)
This research aims to see the effect of tax sanctions, tax services, and tax knowledge on individual taxpayer compliance. The independent variables used are taxation sanctions, tax authorities, and tax knowledge while the dependent variable is taxpayer compliance. The population in this study is an individual taxpayer registered at KPP Pratama Jayapura, using a survey method, by distributing questionnaires directly to taxpayers found at the Jayapura municipal office by researchers. The analytical method used in this study is multiple linear regression with SPSS 16 test. Based on theresults of the analysis show taxation sanctions partially affect the individual taxpayer compliance seen from the significance smaller than 0.05, namely (0.008), tax authorities' services affect complianceIndividual taxpayers seen from the significant value is smaller than 0.05, that is (0,000), and knowledge of taxation affects the individual taxpayer compliance seen from the significance smallerthan 0.05, that is (0.007).